2023
DOI: 10.3389/fpls.2023.1100827
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-mediated development and abiotic stress tolerance in plants

Abstract: Melatonin is a multifunctional molecule that has been widely discovered in most plants. An increasing number of studies have shown that melatonin plays essential roles in plant growth and stress tolerance. It has been extensively applied to alleviate the harmful effects of abiotic stresses. In view of its role in regulating aspects of plant growth and development, we ponder and summarize the scientific discoveries about seed germination, root development, flowering, fruit maturation, and senescence. Under abio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 134 publications
0
17
0
Order By: Relevance
“…In contrast, IAA, GA 3 , and CTK play active roles in delaying leaf senescence. MT can alleviate the inhibition of senescence by regulating IAA, GA 3 , and CTK biosynthesis [ 53 ]. The findings of this study were consistent with previous studies affirming that MT delays leaf senescence under DS by up-regulating IAA, GA 3 , and iPA biosynthesis-related genes ( GhYUC5 , GhGA3ox2 , and GhIPT2 ) and increasing the endogenous IAA, GA 3 , and iPA content ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IAA, GA 3 , and CTK play active roles in delaying leaf senescence. MT can alleviate the inhibition of senescence by regulating IAA, GA 3 , and CTK biosynthesis [ 53 ]. The findings of this study were consistent with previous studies affirming that MT delays leaf senescence under DS by up-regulating IAA, GA 3 , and iPA biosynthesis-related genes ( GhYUC5 , GhGA3ox2 , and GhIPT2 ) and increasing the endogenous IAA, GA 3 , and iPA content ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of ROS due to drought stress causes damage to membranes and organelles and extensive cellular activity changes (Ilyas et al, 2021; Shamloo‐Dashtpagerdi et al, 2019; Zhang et al, 2022). Melatonin acts as a potent antioxidant and a plant antioxidant system (AOS) inducer, scavenging ROS and mitigating oxidative damage caused by drought stress (Back, 2021; Zhang et al, 2023). Elevated melatonin contents and increased activities of antioxidant enzymes, including SOD, POD, and CAT, in response to JA, DR, and JA + DR indicate an enhanced antioxidant defense system in wheat, which mitigate oxidative damage to cellular components such as chloroplast and mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that melatonin regulates ABA biosynthesis genes, resulting in better stomatal function under stress conditions (Li et al, 2015). Moreover, melatonin's positive effect on plants' photosynthesis under different stress conditions has been reported (Altaf et al, 2022;Rehaman et al, 2021;Zhang et al, 2023). Melatonin regulates the carbon fixation pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations